Resiliensi Sosial-Ekonomi Petani Kapulaga di Sentra Produksi Kabupaten Banyumas - Nurdiani, Ulfah; Karim, Akhmad Rizqul; Mandamdari, Alpha Nadeira; Sukmaya, Syahrul Ganda (Universitas Galuh, 2026)
Banyumas Regency is the largest producer of cardamom in Central Java. One of the production centres is in Cilongok District, but in 2024 there was a decline due to drought and low selling prices, which reduced farmers' motivation to cultivate cardamom. This condition necessitates the adaptation of agricultural practices to manage the risks arising from climate change and other challenges, ensuring the sustainability of farming activities amid environmental and economic pressures. This study aimed to analyze the resilience level of cardamom farmers in response to climate change and declining market prices. A cross-sectional survey design was employed, and the sampling technique used was cluster sampling, involving 50 cardamom farmers in Cilongok District. Data were analyzed using descriptive statistics and the Livelihood Vulnerability Index (LVI) approach. Based on the analysis, the LVI score was (0.55), which indicates a moderate to high level of vulnerability. The exposure index was (0.51), reflecting considerable exposure to climatic variability. The sensitivity index was (0.44), indicating moderate impacts on health, food security, and water availability, with fluctuating cardamom prices worsening the condition. The adaptive capacity index scored the highest at (0.68), suggesting a low adaptive capacity among farmers, mainly due to advanced age, low education levels, and limited institutional support. These findings underscore the urgency of implementing adaptation strategies such as technical training, strengthening of farmer organizations, expanding market access, and policy interventions to reduce vulnerability and enhance the resilience of cardamom farmers to climate variability and price instability.